2005
DOI: 10.1007/s11244-005-2529-x
|View full text |Cite
|
Sign up to set email alerts
|

Wet hydrogen peroxide catalytic oxidation (WHPCO) of organic waste in agro-food and industrial streams

Abstract: This review discusses the use of iron-or copper-based solid catalysts in the wet oxidation using H 2 O 2 as oxidant of organic molecules present in agro-food and industrial waste aqueous streams. After an introduction on the advantages and limits of using wet hydrogen peroxide catalytic oxidation (WHPCO) as opposite to wet air catalytic oxidation (WACO), the contribution shortly analyses recent results in the field in order to evidence new trends and open issues. More specific examples discussed regard the per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
100
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(101 citation statements)
references
References 103 publications
1
100
0
Order By: Relevance
“…Different from other published reviews, which have focused on the preparation and performance of the catalysts (Dhakshinamoorthy et al, 2012;Garrido-Ramirez et al, 2010;Navalon et al, 2010a;Nidheesh, 2015;Perathoner and Centi, 2005), this article reviews the fundamental interfacial mechanisms of the heterogeneous Fenton reactions catalyzed by iron-based materials, which may also provide insights for the enhancement of heterogeneous Fenton reactions with additional energy, such as ultraviolet and visible light (UV-Vis), electricity, and ultrasound.…”
Section: Introductionmentioning
confidence: 99%
“…Different from other published reviews, which have focused on the preparation and performance of the catalysts (Dhakshinamoorthy et al, 2012;Garrido-Ramirez et al, 2010;Navalon et al, 2010a;Nidheesh, 2015;Perathoner and Centi, 2005), this article reviews the fundamental interfacial mechanisms of the heterogeneous Fenton reactions catalyzed by iron-based materials, which may also provide insights for the enhancement of heterogeneous Fenton reactions with additional energy, such as ultraviolet and visible light (UV-Vis), electricity, and ultrasound.…”
Section: Introductionmentioning
confidence: 99%
“…Various abatement techniques including biological, thermal, and chemical treatments have been developed in the last few years for the detoxification of organic pollutants [2,3]. Among these techniques, catalytic wet peroxide oxidation (CWPO) appears to be a promising field of study, which has been reported to be effective for the near ambient degradation of soluble organic pollutants, because it can provide a nearly complete degradation [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to these purification technologies, catalytic wet peroxide oxidation (CWPO) has shown excellent removal efficiency for several organic compounds, such as phenol, carboxylic acids and industrial effluents [26,27,28,29,30,31]. CWPO was adapted from a classical Fenton process [32], which has been referred to as an economical alternative to wastewater treatment techniques [33] because it requires only basic equipment and operates at ambient-like pressure and temperature [34,35].…”
Section: Introductionmentioning
confidence: 99%